2008
DOI: 10.13057/biofar/f060203
|View full text |Cite
|
Sign up to set email alerts
|

Effect of garlic (Allium sativum) extract on reduction of total cholesterol and HDL cholesterol ratio in hypercholesterolemic rats

Abstract: Priskila M, Ariningrum D, Suparyanti ES. 2008. Effect of garlic (Allium sativum Linn.) extract on reduction of total cholesterol and HDL cholesterol ratio in hypercholesterolemic rats (Rattus norvegicus). Biofarmasi 6: 45-51. Garlic has been widely recognized as herbal medicine for prevention and treatment of cardiovascular disease, atherosclerosis, and hyperlipidemia. The main bioactive compound, allicin, can influence cholesterol metabolism, reduce total cholesterol and increase HDL cholesterol. The purpose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…High cholesterol levels in the body have been considered a modifiable risk factor which is evident by the fact that plasma cholesterol at levels >200 mg/dL causes 4.4 million deaths in a year (Brouwers et al 2012;Gosh and Gosh 2012). Various types of cholesterol have been reported that include total cholesterol (TC), consisting of all the cholesterols combined; HDL cholesterol, often referred to as good cholesterol that carries cholesterol from the peripheral cells to the liver; and LDL cholesterol often called bad cholesterol that carries cholesterol from the liver to the peripheral cells (Sacks and Katan 2002;Priskila et al 2008;Siri-Tarino et al 2010). The abnormal lipid levels result from an alteration in lipid metabolism, an unhealthy lifestyle, including a high-fat diet, and other lifestyle factors like being overweight, heavy alcohol use, and lack of exercise (Bassam 2013).…”
Section: Introductionmentioning
confidence: 99%
“…High cholesterol levels in the body have been considered a modifiable risk factor which is evident by the fact that plasma cholesterol at levels >200 mg/dL causes 4.4 million deaths in a year (Brouwers et al 2012;Gosh and Gosh 2012). Various types of cholesterol have been reported that include total cholesterol (TC), consisting of all the cholesterols combined; HDL cholesterol, often referred to as good cholesterol that carries cholesterol from the peripheral cells to the liver; and LDL cholesterol often called bad cholesterol that carries cholesterol from the liver to the peripheral cells (Sacks and Katan 2002;Priskila et al 2008;Siri-Tarino et al 2010). The abnormal lipid levels result from an alteration in lipid metabolism, an unhealthy lifestyle, including a high-fat diet, and other lifestyle factors like being overweight, heavy alcohol use, and lack of exercise (Bassam 2013).…”
Section: Introductionmentioning
confidence: 99%